Effects of a Technology Supported Project Based Learning (TS-PBL) Approach on the Success of a Mobile Application Development Course and the Students’ Opinions - Özdamlı, Fezile; Turan, Burcu (TEM Journal, 2017)
Similar to traditional desktop software development processes, teamwork is a necessity in the mobile application development process. Thus, the aim of this study is to examine the effects of the technology supported project-based learning approach in mobile application development courses on the academic achievement of students and to clarify the engineering students’ opinions. A total of 130 engineering students from the Department taking mobile application development courses were the participants of this study. The lessons progressed in one group in the form of technology supported project-based learning steps, while in the other group, they were conducted using traditional methods. Based on the results, the practical implementation of a mobile application with a TS-PBL approach in engineering students’ education will be discussed.